Bilateral Pulmonary Langerhans's Cell Histiocytosis is Surgical Challenge in Children: A Case Report - Soyer, Tutku; Özyüksel, Gül; Türer, Özlem Boybeyi; Çakmakkaya, Kübra; Yavuz, Sinan; Yalçın, Bilgehan; Orhan, Diclehan; Yalçın, Ebru; Doğru, Deniz; Bayrakçı, Benan; Kiper, Nural; Akyüz, Canan (European Journal of Pediatric Surgery Reports, 2019)
Background Pulmonary Langerhans's cell histiocytosis (PLCH) is a rare cause of interstitial lung disease in children and more than half of the cases are bilateral. Persistent respiratory distress due to spontaneous pneumothorax (SP) in bilateral PLCH may refractory to conservative treatment and posed a great challenge to surgical modalities. A 3-year-old boy with SP due to bilateral PLCH is presented to discuss the surgical options of recurrent and refractory PLCH cases in children.Case Report The patient was admitted to the emergency department with severe respiratory distress and SP. After chest tube insertion, biopsy from neck mass revealed Langerhans's cell histiocytosis. Chemotherapy including vinblastine and prednisone was initiated. Due to persistent respiratory difficulty and air leaks, talc pleurodesis and thoracoscopic bullae excision with pleural decortication were performed. Two months after the admission, due to nosocomial infection and severe respiratory distress, extracorporeal membranous oxygenation (ECMO) support was initiated. The patient was died of ECMO complications on 24th day of ECMO.Conclusion Despite the use of chemotherapy and surgical excision of cystic lesions, bilateral PLCH in children may have lethal outcome. Other treatment options including respiratory support with ECMO and lung transplantation should be considered as last resort of treatment alternative in persistent cases.
Keywords: pulmonary Langerhans's cell histiocytosis; children; bilateral